Media Digital Sebagai Kebutuhan Pembelajaran Bahasa Indonesia Di Era Teknologi - Lusiana Lusiana; Siti Fatimah (Advances In Education Journal, 2025)
Digital media has become an essential requirement for supporting a more engaging, interactive, and effective learning process. At the Lentera Jaya Community Learning Center (PKBM) in East Lampung, some students have difficulty understanding conventional Indonesian language materials, necessitating the use of digital media as a solution to improve language skills and learning motivation. This study aims to analyze the use of digital media in Indonesian language learning, assess its effectiveness, determine student preferences for digital media types, and identify obstacles and challenges faced. This study uses a qualitative descriptive approach, with data collection techniques through observation, interviews, and documentation of 11th-grade students. Data analysis was conducted thematically to identify patterns and meanings in students' learning experiences with digital media. The results showed that digital media was effective in improving students' language skills, including writing, reading, speaking, and creative thinking. Digital media also had a positive impact on learning motivation, as students felt more enthusiastic, motivated, and actively engaged in the learning process. Students tended to prefer digital media that were visual, interactive, and supported collaboration, such as learning videos, online quizzes, and discussion forums. However, obstacles such as limited facilities and infrastructure, varying digital literacy, student time and attention management, and content alignment with the curriculum still needed to be addressed to ensure optimal use of digital media. These findings confirm that strategic integration of digital media can improve the overall quality of Indonesian language learning at PKBM Lentera Jaya.